Influence of carbon tetrachloride on induction of tumours of the liver and kidneys in mice by netrosamines. - Pound, A. W. (Nature Publishing Group, 1978)
Mice were given a single dose of nitrosolimethylamine, nitrosoliethylamine or nitrosomethylethylamine and the yield of tumours and related lesions in the livers determined 12 months later. A hepatonecrotic dose of CCl4 24 or 48 h before the nitrosamines, increased the yields of hepatocellular tumours and proliferative foci in the livers, whereas when given 60 h before the nitrosamines there was no significant effect. IMAGES: